Pengaruh Perlakuan Panas Pasca Pengelasan Terhadap Ketahanan Korosi Baja Kapal Jenis High Tensile Strength (HTS) - Intan Permata Dewi (Fakultas Teknik, 2026)
This experimental study analyzes the influence of Post-Weld Heat Treatment (PWHT) using normalizing variations (800°C, 900°C, and 1000°C) on the corrosion rate of AH36 High Tensile Strength (HTS) ship steel welded with the SMAW method. Utilizing the weight loss method through seawater immersion tests and microscopic observations, the research evaluates the weld joint and Heat-Affected Zone (HAZ). Results indicate that PWHT significantly improves corrosion resistance compared to non-PWHT conditions, which are characterized by unstable phases like martensite or bainite. The PWHT process facilitates recrystallization and microstructural homogenization, reducing electrochemical potential differences and stabilizing grain structures. Quantitative data reveals that optimal heating temperatures effectively lower corrosion rates by inhibiting chloride ion penetration, proving that PWHT is a critical factor in enhancing the durability of ship structures in marine environments.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: HTS AH36 Steel; PWHT; Corrosion Rate; Immersion Test